Hommes trans et handicapés : une analyse croisée du cisgenrisme et du capacitisme - Alexandre Baril (Genre, Sexualité et Société)
Research addressing the intersections between transness and disability and between cisgenderism and ableism are rare in English, and almost nonexistent in French. When we add the dimension of a specific gender—focusing, for example, on disabled trans men—the lack of data is glaring. Because a significant proportion of trans people are also disabled, it seems crucial to better understand their entangled experiences of transness and disability, cisgenderism and ableism. This article is structured around this question : what are the heuristic contributions, both theoretical and political, in thinking about the intersections between trans and disabled masculine realities ? The three objectives are as follows : 1) to propose a literature review of work on these intersections ; 2) to offer an intersectional analysis of the realities of men who are trans and disabled, and of cisgenderist and ableist oppressions ; and 3) to identify the heuristic contributions of intersectional analyses of trans and disabled masculinities.